Le masque objet et le masque du faux-semblant de Jean Lorrain - Ferrety Montiel, Maria Victoria (Verbum – Analecta Neolatina, 2023)
It was at the end of the century and thanks to the decadent movement that a new use was attributed to the mask. Indeed, it allows the enthronement of an expression of interiority where the spirit prevails over the body. Thus, it opens the way to a liberation from social constraints by materialising the human soul, since it is no longer a question of granting the human face a unique representation, but the search for the hermeneutic message that it seems to want to conceal. In Jean Lorrain’s Histoires de masques, the narrator reveals the audacity and transgressions of those who wear masks. Our analysis will focus on the existence of two types of masks: the object mask and the pretense mask. We will question the opposing phenomena of resistance and disappearance, as the mask becomes the problematic and polysemous sign of a society that has lost its bearings.